"Ino" colour aberration in gentoo penguin (Pygoscelis papua) in Antarctica - Juares, Mariana Alejandra (2011)
Two main types of pigments, carotenoids and melanin, primarily determine plumage colouration in birds. Carotenoids are obtained from food, while melanin formation involves metabolic processes and is genetically determined. Melanin pigments comprise pheomelanin (red/brown) and eumelanin (brown/black). Any change in the formation processes of these types of pigments may lead to abnormal colouration of an individual For example, a strong qualitative reduction of both types of melanin defines a colour mutation called "ino". On 15 Dec 2003, an ino chick of a gentoo penguin (Pygoscelis papua); was observed at Stranger Point, 25 de Mayo/King George I, South Shetland (62° 16´ S, 58° 37´ W). The following year, on 5 Dec 2004, an ino prebreeder gentoo penguin was seen at the same locality. During 2006/07 breeding season an ino adult of the same species successfully reared 2 normally coloured chicks. The ino penguin we observed showed pale brown colour in the normally dark areas of the plumage in this species. It had reddish eyes and grey claws. The beak remained orange but the normally dark culmen was grey. In summary, the ino penguin showed a clear reduction of the darkest areas of the body changing from black to pale brown in plumage and from black to grey in other tissues such as beak and claws. Nevertheless, the distinctive colour pattern of a gentoo penguin was still recognisable. To our knowledge this is the 1st report of an ino gentoo penguin, following van Grouwes (2006) classification.